Whole-genome maps of USF1 and USF2 binding and histone H3 acetylation reveal new aspects of promoter structure and candidate genes for common human disorders - Rada-Iglesias, Alvaro; Ameur, Adam; Kapranov, Philipp; Enroth, Stefan; Komorowski, Jan; Gingeras, Thomas R.; Wadelius, Claes (Genome Research, 2008)
Transcription factors and histone modifications are crucial regulators of gene expression that mutually influence each other. We present the DNA binding profiles of upstream stimulatory factors 1 and 2 (USF1, USF2) and acetylated histone H3 (H3ac) in a liver cell line for the whole human genome using ChIP-chip at a resolution of 35 base pairs. We determined that these three proteins bind mostly in proximity of protein coding genes transcription start sites (TSSs), and their bindings are positively correlated with gene expression levels. Based on the spatial and functional relationship between USFs and H3ac at protein coding gene promoters, we found similar promoter architecture for known genes and the novel and less-characterized transcripts human mRNAs and spliced ESTs. Furthermore, our analysis revealed a previously underestimated abundance of genes in a bidirectional conformation, where USFs are bound in between TSSs. After taking into account this promoter conformation, the results indicate that H3ac is mainly located downstream of TSS, and it is at this genomic location where it positively correlates with gene expression. Finally, USF1, which is associated to familial combined hyperlipidemia, was found to bind and potentially regulate nuclear mitochondrial genes as well as genes for lipid and cholesterol metabolism, frequently in collaboration with GA binding protein transcription factor alpha (GABPA, nuclear respiratory factor 2 [NRF-2]). This expands our understanding about the transcriptional control of metabolic processes and its alteration in metabolic disorders.